Surveillance of patients attending a diarrhoeal disease hospital in Bangladesh. Issue 6349 (23rd October 1982) - Stoll, Barbara J; Glass, Roger I; Huq, M Imdadul; Khan, M U; Holt, James E; Banu, Hasina
Abstract : In October 1979 a surveillance system was set up at the International Centre for Diarrhoeal Disease Research, Bangladesh, Hospital at Dacca to study a 4% systematic sample of the 100 000 patients with diarrhoea who come to the hospital for care each year. From December 1979 to November 1980 inclusive, 3550 patients were studied. A recognised pathogenic organism was identified for 66% of patients screened for all pathogens, one-third of whom had a mixed infection with two or more agents. Enterotoxigenic Escherichia coli was the most common enteropathogen detected in all age groups (detection rate 20%), followed by rotavirus (19%), Campylobacter jejuni (14%), and Shigella (12%). Infants and young children (up to 5 years) were most often infected with rotavirus, enterotoxigenic E coli, and C jejuni and older children (5-14 years) had more infections with enterotoxigenic E coli, Shigella, and E histolytica. Surveillance has helped to define the range of disease among patients attending the Dacca Hospital. Sixty-five per cent of patients complained of watery diarrhoea, a presentation that was significantly more common in patients with Vibrio cholerae 0:1 (91%), enterotoxigenic E coli (78%), rotavirus (77%), and C jejuni (71%) than in all patients studied. Dysentery, defined as a history of diarrhoea with blood, was the presenting complaint of 20% of all patients but 55% of those with Shigella. Only patients with V cholerae 0:1 and enterotoxigenic E coli were at increased risk for severe dehydration. In addition surveillance has been used to identify areas where patient care can be improved and to generate new ideas for research.